Kinetics and mechanisms of electrochemical reactions on platinum with solutions of iodine-sodium-iodide in dimethylsulphoxide - Arvia, Alejandro Jorge (1969)
The kinetics and mechanisms of the iodine and tri-iodide ion reduction and iodide and tri-iodide ion oxidation on platinum have been determined, from a study of the electrochemical kinetic behaviour of DMSO solutions containing an iodine/sodium-iodide ratio greater than one. The likely mechanisms are the same as those recently discussed for the iodine—sodium-iodide solutions in acetonitrile, and all comprise consecutive reaction schemes involving, for the processes in the anodic direction, an ion-plus-atom reaction as rate-determining step, and the reverse reaction for the cathodic processes.